Tanggung Jawab Profesional Akuntan dalam Memastikan Kepatuhan terhadap Standar Pelaporan Keuangan - Christian Hadinata; Ardiyansyah Prawirautama Ali; Tries Ellia Sandari (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the professional responsibility of accountants in ensuring compliance with financial reporting standards within an increasingly complex business environment. Accountants play a strategic role in maintaining the credibility, transparency, and reliability of financial information used by various stakeholders. Compliance with financial reporting standards is not merely a technical obligation, but reflects ethical commitment, professional integrity, and accountability to the public. The study adopts a qualitative literature-based approach by analyzing academic journals, professional reports, and regulatory documents related to ethics, professionalism, auditing, and financial reporting standards. The findings indicate that ethical values, professional competence, regulatory frameworks, and audit quality are interconnected factors that significantly influence compliance with financial reporting standards. Furthermore, digital transformation and managerial pressures present new challenges that require accountants to strengthen ethical awareness and professional judgment. Strengthening ethical education, professional development, and audit systems is essential to ensure sustainable compliance and public trust in financial reporting practices.